Description of a new species of Gymnotocinclus from the rio Tocantins basin with phylogenetic analysis of the subfamily Hypoptopomatinae (Siluriformes: Loricariidae) - Roxo, Fábio F.; Silva, Gabriel S. C.; Ochoa, Luz Eneida; Zawadzki, Cláudio H. (Zootaxa, 2017)
Gymnotocinclus canoeiro n. sp. of the Hypoptopomatinae is described from small tributaries of the upper rio Tocantins basin. It is distinguished from G. anosteos by having five characters: (1) the presence of body dermal plates, (2) the pectoral girdle not exposed in ventral view, (3) the pelvic spine longer than pectoral spine in males, (4) the pectoral fin with seven to eight branched rays, and (5) the presence of an adipose fin. Furthermore, maximum likelihood (ML) analysis was used to estimate a molecular phylogeny from previously published data of one nuclear (F-Reticulon 4) and three mitochondrial (16S RNA, COI and CytB) genes. The phylogenetic results revealed the new species as a sister taxon of Gymnotocinclus anosteos within the Otothyrini. We also included samples of Nannoplecostomus eleonorae that appeared sister group to all other Neoplecostomini species, and Plesioptopoma curvidens that appeared within the Neoplecostomini forming a sister clade to all species of Neoplecostomus, except N. ribeirensis and the species of Pareiorhina, except P. rudolphi.